2008
DOI: 10.1073/pnas.0802981105
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of plant benzylisoquinoline alkaloids

Abstract: Benzylisoquinoline alkaloids, such as the analgesic compounds morphine and codeine, and the antibacterial agents berberine, palmatine, and magnoflorine, are synthesized from tyrosine in the Papaveraceae, Berberidaceae, Ranunculaceae, Magnoliaceae, and many other plant families. It is difficult to produce alkaloids on a large scale under the strict control of secondary metabolism in plants, and they are too complex for cost-effective chemical synthesis. By using a system that combines microbial and plant enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
234
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(242 citation statements)
references
References 35 publications
3
234
0
5
Order By: Relevance
“…The availability of large numbers of BIA biosynthetic genes from opium poppy and related plants has facilitated the reconstitution of several pathways leading to the production of (S)-reticuline and (R,S)-reticuline in E. coli (Minami et al 2008) and Saccharomyces cerevisiae (Hawkins and Smolke 2008), respectively. Production of (S)-reticuline in E. coli was initially achieved by supplementing the bacterial culture medium with dopamine, some of which was converted to 3,4-dihydroxyphenylacetaldehyde (3,4-DHPAA) by a heterologously expressed bacterial monoamine oxidase (Minami et al 2008). PR10-type NCS from C. japonica catalyzed the condensation of dopamine and 3,4-DHPAA to (S)-norlaudanosoline, which underwent successive methylations via 6OMT, CNMT and 4′OMT to yield (S)-reticuline.…”
Section: Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of large numbers of BIA biosynthetic genes from opium poppy and related plants has facilitated the reconstitution of several pathways leading to the production of (S)-reticuline and (R,S)-reticuline in E. coli (Minami et al 2008) and Saccharomyces cerevisiae (Hawkins and Smolke 2008), respectively. Production of (S)-reticuline in E. coli was initially achieved by supplementing the bacterial culture medium with dopamine, some of which was converted to 3,4-dihydroxyphenylacetaldehyde (3,4-DHPAA) by a heterologously expressed bacterial monoamine oxidase (Minami et al 2008). PR10-type NCS from C. japonica catalyzed the condensation of dopamine and 3,4-DHPAA to (S)-norlaudanosoline, which underwent successive methylations via 6OMT, CNMT and 4′OMT to yield (S)-reticuline.…”
Section: Microbesmentioning
confidence: 99%
“…In turn, E. coli-generated (S)-reticuline was converted to the aporphine alkaloid magnoflorine via co-culture with a strain of S. cerevisiae engineered to express the C. japonica genes encoding corytuberine synthase (CYP80G2) and an N-methyltransferase. Similarly, (S)-scoulerine was produced using a gene encoding BBe (Minami et al 2008). Alternatively, (R,S)-reticuline was produced in S. cerevisiae from (R,S)-norlaudanosoline.…”
Section: Microbesmentioning
confidence: 99%
“…Escherichia coli was recently engineered to produce the key BIA intermediate (S)-reticuline from glucose or glycerol 18,19 and co-cultured with S. cerevisiae expressing heterologous enzymes to synthesize (S)-magnoflorine and (S)-scoulerine 20 . While production of the key intermediate (S)-reticuline from simple carbon sources in E. coli is an undeniable success, S. cerevisiae is a more attractive host for BIA synthesis, due to its superior ability to express the cytochrome P450s common in downstream alkaloid synthesis 21 .…”
mentioning
confidence: 99%
“…Instead, dopamine was converted to 3,4-dHPAA by MAO which was further condensed with the remaining dopamine to form S-laudanosoline. [262] Production of dopamine took place by the action of tyrosine/dopa decarboxylase (TYDC). Therefore, expression of TYDC leads to the production of dopamine (from L-DOPA) and tyramine (from tyrosine) at the same time.…”
Section: Enzyme Engineeringmentioning
confidence: 99%
“…Minami et al reported the very first microbial production of S-reticuline by feeding the precursor, dopamine. [262] Dopamine was then converted to 3,4-dHPAA by monoamine oxidase (MAO) which was further condensed with the remaining dopamine to form S-laudanosoline by norcoclaurine synthase (NCS). Then, by the additional expression of 6-O-methyltransferase (6OMT), coclaurine N-methyltransferase (CNMT), and 3′-hydroxy-N-methylcoclaurine 4′-O-methyltransferase (4′OMT) in E. coli, S-reticuline was produced with a titer of 11 mg L −1 from 5 × 10 −3 m of exogenously fed dopamine (Figure 2).…”
Section: Introduction Of Heterologous Genesmentioning
confidence: 99%